Early Childhood Caries: Prevalence and Risk Factors in Seoul, Korea - Bo-Hyoung Jin, DDS, PhD; Deuk-Sang Ma, DDS, PhD; Hyock-Soo Moon, DDS, PhD; Dai-H Paik, DDS, PhD; (Blackwell Synergy, 2003)
The purpose of this study was to determine the prevalence of early childhood caries (ECC), including noncavitated lesions (dr ), in children 6-59 months of age in relation to socioeconomic factors, feeding practices, and oral health behaviors in Seoul, Korea